Characterization of Y-3 receptor-mediated synaptic inhibition by chimeric neuropeptide Y-peptide YY peptides in the rat brainstem - Glaum, SR; Miller, RJ; Rhim, H; Maclean, D; Georgic, LM; MacKenzie, RG; Grundemar, L (WILEY-BLACKWELL, 1997)
1 Neuropeptide Y (NPY) and peptide YY (PYY) act at receptors referred to as Y-1 and Y-2, while the Y-3 receptor is specific to NPY and does not recognize PW. The effects of NPY, its related peptides and a series of newly constructed chimeric NPY-PYY peptides were examined on excitatory and inhibitory postsynaptic currents (e.p.s.cs and i.p.s.cs, respectively) in rat dorsomedial nucleus tractus solitarius (NTS) neurones recorded in coronal brainstem slices. Monosynaptic activity was evoked by electrical stimulation in the region of the tractus solitarius. 2 NPY (5-500 nM) inhibited e.p.s.cs and i.p.s.cs in a concentration-dependent manner. In contrast, PW (500 nM) failed to affect either e.p.s.cs or i.p.s.cs. The N- and C-terminal parts of a series of chimeric NPY-PYY peptides were joined at positions where NPY and PW sequences differ. In binding experiments the chimeric peptides were all about equipotent with NPY and PW in displacing [I-125]-PYY from Y-1 and Y-2 binding sites on SK-N-MC cells and rat hippocampus respectively. 3 In the whole cell voltage clamp recordings of NTS neurones, NPY(1-23)-PW(24-36) and NPY(1-14)-PW(15-36) evoked a concentration-dependent inhibition of e.p.s.cs and i.p.s.cs, while NPY(1-7)-PYY(8-36) and NPY(1-3)-PYY(4-36) were inactive. The only differences in amino acid residues between NPY(1-14)-PW(15-36) and NPY(1-7)-PW(8-36) reside in positions 13 and 14. 4 Furthermore, [Pro(34)]NPY (500 nM) was equivalent in potency to NPY itself at inhibiting monosynaptic transmission in NTS, while [Leu(31),Pro(34)]NPY and pancreatic polypeptide (both at 500 nM) failed to affect synaptic transmission. 5 The present study has shown that NPY acts at Y-3 receptors to suppress both excitatory and inhibitory currents in the NTS. The different efficacy of the chimeric NPY-PW peptides suggests that positions 13 and 14 are of great importance for Y-3 receptor recognition. Finally, this receptor type readily recognizes [Pro(34)]NPY, but not [Leu(31),Pro(34)]NPY.
Keywords: NUCLEUS-TRACTUS-SOLITARIUS; ADRENAL CHROMAFFIN CELLS; PANCREATIC-POLYPEPTIDE; FUNCTIONAL EXPRESSION; SIGNAL EPITOPES; TRANSMISSION; GLUTAMATE; CLONING; NEURONS; MODULATE